Destins de clandestins by Josué Guebo : a rhetoric of illegal immigration for the Renaissance of Africa. (Ponti/Ponts. Langues, littératures, civilisations des pays francophone, 2025)
This reflection focuses on the issue of illegal immigration. Starting from the sociocritical methodological axis, it strives to give the reasons which justify this clandestine migratory phenomenon from the colonialist myth of the prestige conferred on the metropolis to the painting of rampant misery on the continent by putting a point of honour to portray the poor governance of political regimes at the head of African states since most illegal migrants are far from being poor. This is why the analysis is finally presented as a call for the constitution of a real African Union (A. U.) carried by the values of good governance, the only guarantee of incitement of Africans to abandon the clandestine migratory adventure in to participate in the development of the continent for a certain African Renaissance.
Keywords: Illegal immigration; Poor governance; African Union, Good; governance; African Renaissance